2019
DOI: 10.1186/s12888-019-2182-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of brain-derived neurotrophic factor levels and depressive symptoms in young adults with acne vulgaris

Abstract: Background: Brain-derived neurotrophic factor (BDNF) is one of the proteins that contributes to the survival, growth, maintenance of neurons, and plays important roles in the pathophysiology of depression. It has been reported that depression is closely associated with the pathogenesis of acne vulgaris disease. But, there is no report of serum BDNF levels in patients with acne vulgaris. The study aimed to determine the potential association between BDNF and depressive symptoms in young adults with acne vulgari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
(80 reference statements)
2
11
1
2
Order By: Relevance
“…For example, Xue et al 37 showed that 24‐hour sleep deprivation before surgery increased pain sensitivity and was associated with higher BDNF levels. The depression severity did not correlate with BDNF, which is incompatible with previous studies 38,39 . Perhaps, aforementioned chronic inflammation changed this relation; nevertheless, in patients with psoriasis, this association was demonstrated 39,40 .…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…For example, Xue et al 37 showed that 24‐hour sleep deprivation before surgery increased pain sensitivity and was associated with higher BDNF levels. The depression severity did not correlate with BDNF, which is incompatible with previous studies 38,39 . Perhaps, aforementioned chronic inflammation changed this relation; nevertheless, in patients with psoriasis, this association was demonstrated 39,40 .…”
Section: Discussioncontrasting
confidence: 83%
“…The depression severity did not correlate with BDNF, which is incompatible with previous studies. 38,39 Perhaps, aforementioned chronic inflammation changed this relation; nevertheless, in patients with psoriasis, this association was demonstrated. 39,40 The results obtained can also be influenced by the questionnaires used to assess depression.…”
Section: F I G U R Ementioning
confidence: 97%
“…In this study, we evaluated the methylation level at specific CpG sites in BDNF promoter IV. The brain-derived neurotrophic factor is a neurotrophin that has been widely associated with major depressive disorder since abnormalities in its expression produce dysfunction in circuits that compromise emotional and cognitive functions ( 24 , 62 , 63 ). Our association results for the CpG3 site in BDNF promoter IV suggest that individuals with elevated methylation levels are less likely to show a depressive phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…There were significantly lower BDNF levels in patients than in controls with statistically significant negative correlations between serum levels of BDNF and perceived stress scale scores, according to Mikhael, Hamed, Mansour, and Abdelrahman (2019). In their study, He et al (2019) observed that serum BDNF levels were markedly decreased in patients with depression compared with patients without depression and healthy cases. The optimal cutoff value of serum BDNF levels as an indicator for screening of depression was estimated to be 12.28 ng/ml, which yielded a sensitivity of 72%, specificity of 85%, a true-positive rate of 72%, and a false-positive rate of 15% in young Chinese acne vulgaris patients.…”
Section: Acne and Risk Of Depressionmentioning
confidence: 93%